2015
DOI: 10.1515/jpm-2014-0382
|View full text |Cite
|
Sign up to set email alerts
|

Strain at the internal cervical os assessed with quasi-static elastography is associated with the risk of spontaneous preterm delivery at ≤34 weeks of gestation

Abstract: Aim To evaluate the association between cervical strain assessed with quasi-static elastography and spontaneous preterm delivery. Methods Quasi-static elastography was used to estimate cervical strain in 545 pregnant women with singleton pregnancies from 11 weeks to 28 weeks of gestation. Cervical strain was evaluated in one sagittal plane and in the cross-sectional planes of the internal cervical os and external cervical os. The distribution of strain values was categorized into quartiles for each studied r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 89 publications
1
33
0
1
Order By: Relevance
“…The presence of soft tissue in the area of the internal os turned out to be associated with increased risk of preterm delivery. However, no significant associations were found between the risk of preterm labor and elastographic characteristics of the whole cervix and external os, which is consistent with the findings reported by Swiatkowska-Freund et al and Wozniak et al3336…”
Section: Preterm Deliverysupporting
confidence: 91%
“…The presence of soft tissue in the area of the internal os turned out to be associated with increased risk of preterm delivery. However, no significant associations were found between the risk of preterm labor and elastographic characteristics of the whole cervix and external os, which is consistent with the findings reported by Swiatkowska-Freund et al and Wozniak et al3336…”
Section: Preterm Deliverysupporting
confidence: 91%
“…Furthermore, Wozniak et al . and Hernandez‐Andrade et al . found that stiffness of the internal os which seemed to be denser than surrounding tissues provided relatively high sensitivity, specificity, negative and positive predictive values in prediction of preterm labor, thus supporting a popular hypothesis that this anatomical region is crucial for maintaining pregnancy and may play a main role in the mechanism of cervical ripening and labor onset.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have investigated the predictability of preterm birth using cervical elastography in mid-pregnancy. Table 2 summarizes 5 recent articles that assessed the use of strain elastography of the cervix to predict spontaneous preterm birth [ 20 21 22 23 24 ]. These studies evaluated a larger area than that used in labor induction, by analyzing several ROIs ( Fig.…”
Section: Current Use Of Cervical Elastographymentioning
confidence: 99%